A Combined Fluidic Force-Magnetic Field Driven Self-Assembly Technique to Yield Fully Functional Single Nanowire Electroanalytical Devices. Issue 7 (1st January 2016) - Wahl, Amélie; Pescaglini, Andrea; O'Connell, Dan; Dawson, Karen; Iacopino, Daniela; Quinn, Aidan J.; O'Riordan, Alan
Abstract : In this work, we fabricated fully integrated single nanowire-based electrochemical devices at silicon chip substrates using a novel combined self-assembly approach. To this end, highly uniform striped nanowires composed of a platinum body and a magnetic cobalt-platinum tip were synthesized by template electrodeposition. A combination of fluidic/capillary assembly and magnetic assembly was employed to orient and trap nanowires, respectively, at pre-defined nickel receptor sites at silicon chip substrates. Post assembly integration was performed by first depositing gold interconnection metallization, with on-chip gold counter and pseudo-reference electrodes and a passivation layer (to ensure exclusive contact between the electrodes and electrolyte) to yield fully integrated devices. Peripherally located probe pads enabled facile and direct electrical connection to the working, counter and pseudo-reference electrodes. Fully integrated nanowire devices displayed characteristic Ohmic responses and low contact resistances. Finally, preliminary electrochemical measurements in ferrocene monocarboxylic acid solution in phosphate buffer were also carried out to demonstrate the potential use of these devices in electrochemical applications.